Spherical Principal Series of Quantum Harish-Chandra Modules - Bershtein, O.; Stolin, A.; Vaksman, L. (Журнал математичної фізики, аналізу, геометрії, 2007)
The nondegenerate spherical principal series of quantum Harish-Chandramodules is constructed. These modules appear in the theory of quantumbounded symmetric domains. Mathematics Subject Classification: 17B37, 22E45